2019
DOI: 10.5371/hp.2019.31.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Debridement, Antibiotics and Implant Retention for Early Periprosthetic Infections of the Hip: Outcomes and Influencing Factors

Abstract: Purpose Debridement, antibiotics and implant retention (DAIR) is commonly performed and widely accepted for the treatment of acute infections following hip arthroplasty. The aims of this study were to: i) determine the DAIR success rate in treating acute postoperative and hematogenous periprosthetic infections of the hip at a tertiary hospital, ii) identify possible outcome predictors, and iii) analyze clinical and radiological outcomes. Materials and Methods We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
5
0
2
Order By: Relevance
“…Comparing these to Iza et al results (23), who reported on 22 knees with PJI underwent DAIR only with an overall success rate of 77%, will make it unsatisfactory. However, Flierl et al results are significantly better when compared to Uriarte et al (24) who reported on 26 hips with PJI underwent DAIR only procedure with an overall success rate of 26.9%. A literature review by Tsang et al (25), included 1296 patients who underwent DAIR for the management of PJI in hip arthroplasty, concluded that the only determinants of outcome is the timing of DAIR after the onset of symptoms of infection.…”
Section: Discussionmentioning
confidence: 85%
“…Comparing these to Iza et al results (23), who reported on 22 knees with PJI underwent DAIR only with an overall success rate of 77%, will make it unsatisfactory. However, Flierl et al results are significantly better when compared to Uriarte et al (24) who reported on 26 hips with PJI underwent DAIR only procedure with an overall success rate of 26.9%. A literature review by Tsang et al (25), included 1296 patients who underwent DAIR for the management of PJI in hip arthroplasty, concluded that the only determinants of outcome is the timing of DAIR after the onset of symptoms of infection.…”
Section: Discussionmentioning
confidence: 85%
“…Uriarte et al reported a significantly higher failure rate when DAIR was performed by general orthopaedic surgeons compared with hip surgeons 25 . Experience was not considered in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the treatment success rate of DAIR is highly variable, ranging from approximately 30% to 90% efficacy [83,[116][117][118]. One factor not previously discussed that can determine the success of a DAIR procedure is early intervention [100].…”
Section: One-stage and Dairmentioning
confidence: 99%